Managing pearly prepuce - Active communication and masterly inaction - Faridi, M M A; Sharma, Ankit (Indian Journal of Child Health, 2017)
Epstein pearls are small inclusion cysts and are found on the hard palate of the newborn infants in the early neonatal age. These may be present on the prepuce and are referred as prepucial Epstein pearl. Epstein pearls need no treatment but parental anxiety needs to be addressed by active communication and counselling.